A USER PERCEPTION MODEL CONCERNING SAFETY AND SECURITY OF PARATRANSIT SERVICES IN BANDUNG, INDONESIA - Tri Basuki Joewono; Hisashi Kubota (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2005)
Abstract Safety and security in public transportation, Angkutan Kota or paratransit included, are among the commonly poor aspects in Indonesia. The objective of this research is to describe user perception of safety and security aspects in paratransit operation and to develop a model to predict and explain user choice in the future when there is an improvement. Users stated that the conditions of safety and security could be categorized as fair to dangerous. Realizing the condition, users still want to use paratransit because they have no other mode and paratransit can easily be found. The main reason for safety problems was the low degree of awareness of the driver in operating the car, while the main reason for security problems was the low degree of law enforcement and limited number of policemen (security officers). Users stated that the most responsible stakeholder in safety and security was the operator (driver and owner) and the police. Each aspect has two models using binomial logistic regression, namely a model with and without experience of accidents or criminal incidents. All models seem quite appropriate ones, as shown by their statistical measurement. Incorporating user experience improved the model fitness and improved the model in describing traveler characteristics.Keywords: paratransit, safety, security, perception, model.